Minimizing Production Defects in Bolts Using The Economic Production Quantity (EPQ) Method at PT. Platindo Makmur Sentosa - Yordan Prayoga (International Journal Labs, 2026)
Product defects in the manufacturing industry remain a critical challenge because they affect production efficiency, operational costs, and customer satisfaction. PT. Platindo Makmur Sentosa, a bolt manufacturing company, faces challenges related to high defect rates, inefficient production planning, and difficulties in determining optimal production quantities. This study aims to identify the causes of bolt production defects, evaluate the production process, and determine the economical production quantity using the Economic Production Quantity (EPQ) method to minimize defects and improve production efficiency. This research employed a descriptive quantitative approach supported by direct observation, interviews, production data collection, and literature reviews. The analysis was conducted through defect identification, Pareto analysis, Fishbone Diagram analysis, and EPQ calculations based on production data from October to November 2023. The results showed that the main causes of defects were associated with human factors, materials, methods, machinery, and environmental conditions. The highest defect contributions were found in the FH 12×3 ZINC and TSAK 8×2.1/2 ZINC bolt types. The implementation of the EPQ method reduced production setup frequency and significantly decreased defect rates. For FH 12×3 ZINC bolts, defects decreased by 494 grams (25%), while TSAK 8×2.1/2 ZINC bolts experienced a reduction of 522 grams (45.5%). In conclusion, the EPQ method effectively optimizes production quantities, reduces defects, and improves operational efficiency. The company is recommended to implement structured production planning, conduct regular machine maintenance, and provide operator training to sustain continuous quality improvement.